Analysis of Criminal Offices on Copyrights and its Applications in Indonesia - Sinaga, Wetmen (Advances in Social Sciences Research Journal, 2022)
Copyright is a work of someone’s imagination, who has exclusive rights in the use of his or her copyrighted work so that if there are parties who will use the copyright for commercial purposes, they must first obtain a license (license) from the creator or his proxies and pay royalties. Any party who does not obtain a license as mandated by UUHC will be subject to legal sanctions, both civil and criminal. Copyright crime occurs when someone announces or reproduces a work for commercial purposes without permission from the Creator or Copyright Holder is an infringement and such violation will be subject to criminal sanctions in accordance with the provisions of Article 112 of Law Number 28 of 2014. Criminal offenses in law no. 28 of 2014 concerning Copyright is a complaint offense so that the investigating apparatus cannot take action against parties suspected of committing criminal offenses without a report from the injured party, where this is very detrimental to the rights of the creator in the form of economic rights and moral rights, while in law no. 19 of 2002 concerning Copyright, the regulation of criminal offenses is an ordinary offense, and the investigative apparatus (police and prosecutors) can directly take action against parties committing copyright crimes.